A methodology to globally assess ectodomain shedding using soluble fractions from the mouse brain - Lobete, Miguel; Salinas, Tamel; Izquierdo-Bermejo, Sara; Socas, Silvia; Oset-Gasque, María Jesús; Martín-de-Saavedra, M. Dolores (Frontiers in Psychiatry, 2024)
Ectodomain shedding (ES) is a fundamental process involving the proteolytic cleavage of membranebound proteins, leading to the release of soluble extracellular fragments (shed ectodomains) with potential paracrine and autocrine signaling functions. In the central nervous system (CNS), ES plays pivotal roles in brain development, axonal regulation, synapse formation, and disease pathogenesis, spanning from cancer to Alzheimer's disease. Recent evidence also suggests its potential involvement in neurodevelopmental conditions like autism and schizophrenia. Past investigations of ES in the CNS have primarily relied on cell culture supernatants or cerebrospinal fluid (CSF) samples, but these methods have limitations, offering limited insights into how ES is modulated in the intact brain parenchyma. In this study, we introduce a novel methodology for analyzing shed ectodomains globally within rodent brain samples. Through biochemical tissue subcellular separation, mass spectrometry, and bioinformatic analysis, we show that the brain's soluble fraction sheddome shares significant molecular and functional similarities with in vitro neuronal and CSF sheddomes. This approach provides a promising means of exploring ES dynamics in the CNS, allowing for the evaluation of ES at different developmental stages and pathophysiological states. This methodology has the potential to help us deepen our understanding of ES and its role in CNS function and pathology, offering new insights and opportunities for research in this field.